Long-term follow-up and pregnancy after complete sacrectomy with lumbopelvic reconstruction: case report and literature review. Issue 1 (December 2016) - Barsan, Valentin; Briceño, Valentina; Gandhi, Manisha; Jea, Andrew
Abstract Background Sacrectomy remains a technically complex procedure for resection of malignant pelvic neoplasia. Commonly, postoperative complications include permanent neurological deficits. Only a few studies have reported the long-term functional outcomes of patients who had undergone sacrectomy. Case presentation We previously reported on the utilization of complete sacrectomy and lumbopelvic reconstruction for the management of primary myofibroblastic sarcoma of the sacrum and ilium in a 15-year-old female patient. In this report, we update her postoperative course with an additional 5 years of follow-up and Health-Related Quality of Life (HRQoL) outcomes. During this time period, she gave birth to two healthy full-term babies. Conclusion To the best of our knowledge, this is the first report of pregnancy after total sacrectomy and lumbopelvic reconstruction. We outline some of the challenges in the obstetrical management of this patient.